Perancangan dan Analisis Intrusion Prevention System Berbasis SNORT dan IPTABLES dengan Integrasi Honeypot pada Arsitektur Software Defined Network - Barends, Julian Kevin; Dewanta, Favian; Karna, Nyoman Bogi Aditya (MULTINETICS, 2021)
Software Defined Network is a network architecture that allows the network to be controlled centrally by separating the Control Plane and Data Plane making it easier from the operator's side to manage the network consistently, therefore SDN is believed to be able to replace the existing network which tends to be rigid. But despite the capabilities of the SDN, SDN security is still a major concern. In project, the design of an Snort and IPTables based IPS system that is integrated with the Honeypot system in the Software Defined Network network architecture will be carried out. IPS will detect attacks based on the applied rules and if there is an attack then IPS will give an alert to the Controller which then the Controller will check the database and divert the attack traffic to the Honeypot. The results shows that the accuracy rate is 99.87%, the average detection speed for Port Scanning, Ping of Death, ICMP Flood and TCP SYN Flood attacks are 1.207 s, 1.045 s, 1.047 s, and 1.101 s. While the QoS measurement shows that after the attack is transferred, there is an increase in the Throughput value and a decrease in the Packet Loss value.